Pubertal Development and Anxiety Risk Independently Relate to Startle Habituation during Fear Conditioning in 8 to 14 Year-Old Females - Jackson, Felicia (Dev Psychobiol, 2017)
Reduced habituation to aversive stimuli has been observed during adolescence and may reflect an underlying mechanism of vulnerability for anxiety disorders. This study examined the startle reflex during a fear-learning task in 54 8–14 year-old girls. We examined the relationship between mean startle, startle habituation, pubertal development, and two measures linked to risk for anxiety: behavioral inhibition system (BIS) and the error-related negativity (ERN). Puberty, BIS, and the ERN were unrelated to mean startle; however, each measure modulated startle habituation. Greater pubertal development was associated with reduced startle habituation across the CS+ and CS−. Higher BIS related to a larger ERN, and both were associated with reduced startle habituation specifically to the CS+. All effects were independent of each other. Findings suggest that puberty alters habituation of defense system activation to both threat and safety cues, and this is independent of risk for anxiety, which uniquely impacts habituation to threat cues.